Kryptosporidieinfektion hos nötkreatur : utvärdering av en ny metod för påvisande av subklinisk infektion - Andersson, Sofie (SLU/Dept. of Ruminant Medicine and Veterinary Epidemiology, 2004)
Cryptosporidium parvum is a protozoan parasite causing diarrhoea in many different animal species including cattle and man. It is an important enteric pathogen in neonatal calves and it is the second most common pathogen found in diarrhoeic calves in Sweden. Subclinically infected adult cattle have, in international studies, been shown to shed a low number of oocysts in faeces and this has been recognised as a potential source of infection for new-born calves. The detection methods used for diagnostic purposes are based on microscopic investigation of faecal smears. These methods have a fairly low sensitivity and samples from subclinically infected cattle have to be concentrated before analysis.